2019
DOI: 10.1136/rapm-2019-100608
|View full text |Cite
|
Sign up to set email alerts
|

Dural puncture epidural analgesia for labor: a randomized comparison between 25-gauge and 27-gauge pencil point spinal needles

Abstract: BackgroundThis double-blind, randomized trial compared dural puncture epidural analgesia (DPEA) for labor using 25-gauge and 27-gauge pencil point spinal needles. We hypothesized that both needle sizes would result in similar onset time (equivalence margin=2.5 min) and therefore designed the study as an equivalence trial.MethodsOne hundred and forty patients undergoing labor were randomized to DPEA with 25-gauge (n=70) or 27-gauge (n=70) pencil point spinal needles. After the placement of the epidural catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…Although the motor block degree reported by previous studies was comparable between the DPE and EA techniques for labor analgesia [ 15 , 18 , 24 ], the DPE technique resulted in significantly higher motor block scores at each time point than the EA technique in our study. One possible reason is that the concentration of local anesthetics was significantly higher than that in other studies applied for labor analgesia, in which a low concentration of ropivacaine produced motor-sensory separation.…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…Although the motor block degree reported by previous studies was comparable between the DPE and EA techniques for labor analgesia [ 15 , 18 , 24 ], the DPE technique resulted in significantly higher motor block scores at each time point than the EA technique in our study. One possible reason is that the concentration of local anesthetics was significantly higher than that in other studies applied for labor analgesia, in which a low concentration of ropivacaine produced motor-sensory separation.…”
Section: Discussioncontrasting
confidence: 70%
“…The DPE technique is a modified anesthesia method based on CSE; the dura is punctured using a spinal needle, and local anesthetics are introduced into the epidural space via an epidural catheter instead of directly into the subarachnoid space[ 14 ]. The theoretical basis is that perforation of the spinal dura facilitates the infiltration of local anesthetics into the subarachnoid space[ 15 ]. As early as 1998, Leach et al [ 23 ] observed the translocation of epidural dye into the subarachnoid space through an accidental dural puncture via a tuohy needle (gauge not documented), which verified the theory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations